Building a Course Portfolio with Industry-Institute Collaboration - Hegade, Prakash; Patil, Nirmala; Kanthi, Namita (Journal of Engineering Education Transformations, 2022)
The effective integration strategies of blended learning with traditional, designed a decade ago and proven effective, scalable, and flexible, now put forth several other challenges with delivery and evaluation. Especially for the elective courses, they demand assessments that add value to the course and the student’s resume. The principles of elective design, the delivery tools, and techniques, the number of students, the significance of the course, etc., are some of the major evaluation parameters to be considered for the design of assessment strategies. This paper presents one such evaluation methodology, portfolio design, for the courses delivered in a blended learning model, which can also be adapted to the offline learning model. The model involved problem analysis, concept relation, design thinking, solution approaches, implementation, and presentation in the form of a portfolio. The portfolios were created online using various open source tools. The paper presents the model and design goals in detail. The first offering of the course had course projects, and the second offering had portfolio creation. The grades and attainment have improved in the second offering compared to the first one. There is also improvement in the course attainment where course learning objectives have remained the same. Portfolios are an effective strategy to evaluate one’s course understanding. Portfolios can be an effective way to present the course realizations to the community as justified through the t-test analysis.